Canadian Muskoxen in Central Europe - A Zoo Veterinary Review - Seidel, K.B.; Rowell, J.E. (Rangifer, 1996)
This paper summarizes 29 years of veterinary experience maintaining a herd of muskoxen at the Tierpark Berlin-Friedrichsfelde, Berlin, Germany. The transplanted muskoxen acclimated to the zoo enviroment without fatalities. However, a few striking changes were seen. They exhibit a high sensitivity to sudden changes in weather conditions (especially falling atmospheric pressure); there is a tendency for their qiviut to become sparser with time; rutting and subsequent calving occur later than in their native habitat. Details of medical conditions in both calves and adults ate given along with information on hematology and immobilization.